Dynamics Analysis of Avian Influenza A(H7N9) Epidemic Model - Yun Li; Peng Qin; Juping Zhang (Discrete Dynamics in Nature and Society)
The avian influenza A(H7N9) virus has certain fatal effects on human. In this paper, a mathematical model describing the transmission dynamics of avian influenza A(H7N9) between human and poultry is investigated. The basic reproduction number of the model is obtained by applying the method of the next generation matrix. Then the local and global stability of the equilibria are proven. At last, we use numerical simulations to verify the theoretical results.